Are Conference Posters Being Cited? - Haupka, Nick; Schröer, Cäcilia; Hauschke, Christian (Frontiers in Research Metrics and Analytics, 2021)
We present a small case study on citations of conference posters using poster collections from both Figshare and Zenodo. Citation data was taken from DataCite, Crossref and Dimensions. Primarily, we want to know to what extent scientific posters are being cited and thereby which impact posters potentially have on the scholarly landscape and especially on academic publications. Our data-driven analysis reveals that posters are rarely cited. Citations could only for be found for 1,1 % of the posters in our dataset. A limitation in this study however is that the impact of academic posters was not measured empirical but rather descriptive.